A commentary on expectations of healthcare professionals when applying the international continence society standards to basic assessment of lower urinary tract function. (15th August 2018) - Drake, Marcus J.; Abrams, Paul
Abstract : The International Continence Society (ICS) has sustained a drive to improve the clinical assessment of lower urinary tract function for many years. Increasingly, healthcare professionals (HCPs) engage with the guidance, and patients benefit from the precision that results when their carers apply a sensible and logical approach to assessment. The current supplementary issue of Neurourology and Urodynamics (NAU) summarizes the fundamentals derived from major ICS initiatives, emphasizing what HCPs must know when dealing with these patients, regardless of the medical discipline in which they work. It also introduces the basics of urodynamics testing to trainees and HCPs who may refer patients for testing. In this editorial review we draw out some additional points of consideration. We emphasize the need to avoid using terms in a clinical context that could imply causative mechanism, until the mechanism has actually been identified. We caution against the use of severity thresholds, until there is proper data to justify their application for any given patient group. Finally, we provide a description of the philosophical basis of urodynamics testing, including videourodynamics. This commentary should be read in the context of the other articles provided in the NAU supplement.